2005
DOI: 10.1016/j.orthres.2004.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selected wound antiseptics on adult articular cartilage (bovine sesamoid bone) in the presence of Escherichia coli and Staphylococcus aureus

Abstract: After removing an inoculum of 108-10' cfu of Esckrrichiu coli (E. cdi)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 29 publications
0
53
0
5
Order By: Relevance
“…In contrast to iodine, no toxic effects of polihexanide on wound healing have as yet been reported in the literature [10,12,16] .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to iodine, no toxic effects of polihexanide on wound healing have as yet been reported in the literature [10,12,16] .…”
Section: Discussionmentioning
confidence: 99%
“…A comparative in vitro study of cell toxicity reported best results of polyhexanide compared to octenidine and povidone-iodine [10] . Thus far no toxic effects of polyhexanide on wound healing have been reported in the literature [4,6,11,12] , whereas polyhexanide shows a good microbicidal activity and therefore qualifies for reduction in bacterial populations on the wounds [2,13,14] . Accordingly, in our study no infection was seen.…”
Section: Discussionmentioning
confidence: 99%
“…PHMB was effective against planktonic E. coli and S. aureus as well as P. aeruginosa in suspension and biofilms [37,38,39,40,41,42,51,52,53]. In addition, PHMB was also effective against E. faecalis and C. albicans [54], as well as against intracellular bacteria such as Chlamydia sp.…”
Section: Resultsmentioning
confidence: 99%